Risk Detection and Assessment in Wood and Metal Products Industries using HAZAN Method - Hamed Biglari (Journal of Global Pharma Technology, 2017)
Developing and advancing technology in the industries has increased the number of risks at work environment and the number of workers at risk as well. These risks and the risk factors need to be managed, assessed, and controlled using systematic methods. Therefore, the present study is aimed at assessing and detecting risks in wood and mental products industries using HAZAN method. Data gathering was done using HAZAN worksheet, observation, walking and talking method, risk detecting checklists, technical documents, and plots available. The findings represented 137 risks at workshop, out of which 2.92% were 1st rank (unacceptable), 2.92% were 2nd rank (undesirable), 85.4% were 3rd rank (acceptable if controlled), and 8.76% were 4th rank (acceptable). Most of the risks were found at MDF section (n 30), metal assembly (n 28), metal works (n 27), and MDF assembly (n 23). In addition, high risks jobs were bending, electrical welding, PVC work, and guillotine work. The results showed that 3rd rank risks were the largest group of risks and this showed that great improvement could be made in cutting the number of accidents and financial and life loss by controlling these risks. It is notable that 1st rand risks should be controlled immediately using engineering and administrative controls and 2nd rank risks shall be turned into 3rd rank risks in a reasonable time frame. With regard to 3rd rank risks, we need to make sure of availability of controls; and the 4th rank risks were acceptable. Taking measures such as safety training and permanent supervision by the safety authorities were also effective to minimize the risks.Keywords: Risk, assessment, HAZAN method, industrials products, workers risk